2012
DOI: 10.1109/tsp.2012.2193577
|View full text |Cite
|
Sign up to set email alerts
|

Blind Channel Estimation for Amplify-and-Forward Two-Way Relay Networks Employing $M$-PSK Modulation

Abstract: We consider the problem of channel estimation for amplify-and-forward (AF) two-way relay networks (TWRNs). Most works on this problem focus on pilot-based approaches which impose a significant training overhead that reduces the spectral efficiency of the system. To avoid such losses, this work proposes blind channel estimation algorithms for AF TWRNs that employ constant-modulus (CM) signaling. Our main algorithm is based on the deterministic maximum likelihood (DML) approach.Assuming M-PSK modulation, we show… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
38
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 44 publications
0
38
0
Order By: Relevance
“…Compared with other TWRN protocols, such as digital network coding in which the relay performs XOR operations on bit streams from the two users [1,5], it has been shown that PNC requires smaller number of time slots for full information exchange [4]. The performance of TWRNs with PNC has been thoroughly analysed from the perspective of capacity [6,7], bit error rate (BER) [1,4,[8][9][10][11][12][13] and practical issues such as channel estimation and synchronisation [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other TWRN protocols, such as digital network coding in which the relay performs XOR operations on bit streams from the two users [1,5], it has been shown that PNC requires smaller number of time slots for full information exchange [4]. The performance of TWRNs with PNC has been thoroughly analysed from the perspective of capacity [6,7], bit error rate (BER) [1,4,[8][9][10][11][12][13] and practical issues such as channel estimation and synchronisation [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Unidirectional or one-way relaying supports in communication from a source to a destination user and has been studied in the literature [1]. On the other hand, in two-way relaying networks (TWRNs), the flow of information is bidirectional and the two users exchange data simultaneously with the relation of an intermediate relay node [2]. The comparison with one-way half-duplex relaying, bidirectional relaying is a spectrally more efficient relaying protocol [2].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in two-way relaying networks (TWRNs), the flow of information is bidirectional and the two users exchange data simultaneously with the relation of an intermediate relay node [2]. The comparison with one-way half-duplex relaying, bidirectional relaying is a spectrally more efficient relaying protocol [2]. Both amplify-and-forward and decode-and-forward protocols have been designedfor TWRNs.…”
Section: Introductionmentioning
confidence: 99%
“…The CRB for the estimation of the channel parameters in a one-way AF cooperative system using flat-fading channels has been obtained in [18], while in [19], the CRB is obtained for an AF and DF system in which multiple frequency offsets are considered. Lower bounds for the two-way relaying channel, in which two terminals aided by a relay communicate with one another, have been obtained in [20][21][22][23] for the AF protocol.…”
Section: Introductionmentioning
confidence: 99%